Surveillance of microorganisms associated with dental caries patients attending at a Tertiary Care Indian Teaching Hospital - Smarita Lenka; Priyanka Debta; Mahesh Chandra Sahu (Apollo Medicine)
Backgrounds: Dental caries patients are developed day by day in all age groups and predominantly in children. It is caused due to microorganisms mainly. Here, we find the organisms associated with dental caries of patients attending at Institute of Dental Science, Bhubaneswar, India. Materials and Methods: This prospective study was carried out from February to May 2018 at Institute of Dental Science, Bhubaneswar, India. A total number of 135 samples were collected from dental caries patients and processed in different agar media for identification of organisms, and the percentage of antibiotic susceptibility was evaluated. Results: Out of 135 patient samples, 112 organisms were isolated and identified with both culture and biochemical tests. Among all, 9 Enterococcus sp. (6.66%), 27 coagulase-negative Staphylococcus aureus sp. (20%), 6 Bacillus sp. (4.44%), and 30 Streptococcus sp. (22.22%) were found as Gram-positive cocci; 3 Acinetobacter sp. (2.22%), 6 Pseudomonas sp. (4.44%), 21 Shigella sp. (15.55%), and 6 Citrobacter freundii sp. (4.44%) were identified as Gram-negative bacteria; and 6 Candida glabrata (4.44%), 3 Candida albicans (2.22%), and 3 Candida tropicalis (2.22%) were identified as budding yeast colonies. In antibiotic resistance patterns, it was revealed that penicillin is the most resistance (92%) and gentamycin is the most sensitive antibiotic (79.2%) for bacteria associated with dental caries. Conclusion: Dental caries caused due to microbial infection is cured with antibiotics. Out of all antibiotics, gentamicin is more sensitive and preferable for dental caries with this study. Hence, a clinician can prescribe gentamicin beside amoxicillin and cefixime for early treatments.